Papel da capsaicina de uso tópico em modelo murino de alergia alimentar - Elandia Aparecida dos Santos (2016)
Food allergy is an immediate hypersensitivity reaction mediated by IgE which occurs with the ingestion of allergenic foods after previous sensitization. It is considered a major problem of public health worldwide, affecting about 7% of children and 2% of adults, with increasing prevalence in developed and developing countries. Hypothetically, anti-inflammatory agents could contribute to the control some allergy symptoms. A candidate for this purpose is the capsaicin (8-methyl-N-vanillyl-6- nonenamide), the main pungent component of red pepper, having analgesic and anti- inflammatory actions when applied topically. This study evaluated the effect of topical treatment of capsaicin in some food allergy maniestations. For this purpose BALB/c mice were sensitized with ovalbumin (OVA) with subsequent oral challenge with 20% egg yolk solution. From the oral challenge to euthanasia, animals of capsaicin group (CAP) were topically treated with a capsaicin cream (0.075% in cream base) while the allergic group (ALE) were treated with the cream base (without capsaicin). The results showed that there was an increase in serum IgE and anti-OVA IgG1 in both groups, as expected with thisfrom sensitization protocol. However, compared to allergic group (ALE), animals from CAP group presented a more favorable profile, as suggested by the higher intake of allergen, reduced weight loss, reduced eosinophil and neutrophil infiltrations (assessed indirectly by the activity of the enzymes EPO and MPO, respectively) and lower production of mucus by goblet cells. The results suggest that topical treatment with capsaicin leads to an improvement of some of the most important manifestations allergy such as intestinal inflammation and weight loss. These effects may be related to inhibition of TRPV1 channel, acting indirectly on CD4+ T cell, mast cells and basophils signaling, increasing their activation threshold and thus decreasing the inflammatory process. Additionally, the improvement of allergen tolerance may be related to the analgesic effect of capsaicin, leading to the nociceptors desensitization via TRPV1, which would allow the higher intake of egg white. More studies are needed to elucidate the mechanisms involved in the use of topical capsaicin front of allergic diseases, especially in food allergy.